A Comparison of Survival Analysis, Threshold Regression and Linear Mixed Models in a Longitudinal Diabetes Clinic Study (2009 – 2013) at Kalafong Hospital with Nephropathy as Outcome - Dzikiti, Loveness Nyaradzo (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2014.